Effects of Prostaglandin E1 and Balloon Atrial Septostomy on Cerebral Blood Flow and Oxygenation in Newborns Diagnosed with Transposition of the Great Arteries - Manuela Cucerea; Maria-Livia Ognean; Alin-Constantin Pinzariu; Marta Simon; Laura Mihaela Suciu; Dana-Valentina Ghiga; Elena Moldovan; Mihaela Moscalu (Biomedicines)
Dextro-transposition of the great arteries (D-TGA) is a critical congenital heart defect that can impact neurodevelopment due to cerebral perfusion and oxygenation disorders followed by alterations in synaptogenesis, gyrification, sulcation, and the microstructure. Brain injuries can occur both pre-operatively and postoperatively, especially white matter injuries, neuronal loss, and stroke. Materials and Methods: In a retrospective study conducted at a tertiary center between 2016 and 2023, we investigated the early effects of Prostaglandin E1 (PGE1) administration and balloon atrial septostomy (BAS) on cerebral blood flow and oxygenation in inborn neonates with D-TGA. Cerebral Doppler Ultrasound in the anterior cerebral artery (ACA) was performed to assess the resistive index (RI), Peak Systolic Velocity (PSV), and End-Diastolic Velocity (EVD) before PGE1, before the BAS procedure, and 24 h after birth. Cerebral regional saturations of oxygen (crSO2) and cerebral fractional tissue oxygen extraction (cFTOE) were evaluated. D-TGA patients were divided into the PGE1 group and the PGE1 + BAS group. Age-matched healthy controls were used for comparison. Results: All 83 D-TGA newborns received PGE1 within two hours after delivery, of whom 46 (55.42%) underwent BAS. In addition, 77 newborns composed the control group. PGE1 administration increased crSO2 from 47% to 50% in the PGE1 group, but lower than in controls at 24 h of life, while cFTOE remained elevated. The RI increased 24 h after delivery (0.718 vs. 0.769; p = 0.000002) due to decreased EDV (10.71 vs. 8.74; p < 0.0001) following PGE1 treatment. The BAS procedure resulted in a significant increase in crSO2 from 42% to 51% at 24 h of life in the PGE1 + BAS group. Doppler parameters exhibited a similar trend as observed in the PGE1 group. Conclusions: PGE1 treatment and BAS are lifesaving interventions that may improve cerebral perfusion and oxygenation in newborns with D-TGA during the transition period, as reflected by increasing SpO2 and crSO2.